Sustainable development in Southeast Asia: The nexus of tourism, finance, and environment - Trung Ha Van; Lee Lichang; Thuan Dang Thanh Quoc (Heliyon)
Southeast Asia's booming tourism and rapid economic growth create a unique setting to explore the interplay between economic development, tourism, and environmental sustainability. This study examines the complex interplay between tourism expansion, financial development, and environmental sustainability in Southeast Asia, specifically from 2000 to 2023. This research aims to fill gaps in previous studies, particularly within the Association of Southeast Asian Nations (ASEAN) context, and to provide a comprehensive understanding of how tourism and financial growth impact environmental outcomes in this region. The Autoregressive Distributed Lag (ARDL) model with Pooled Mean Group (PMG) specifications is utilized to analyze the long-term relationships between these factors while capturing the unique short-run dynamics of individual countries within Southeast Asia. The findings reveal intricate relationships spanning both short-term and long-term dynamics, highlighting the impact of tourism growth on environmental factors such as increased renewable energy use, Carbon Dioxide (CO2) emission, and ecological footprints. One-way causality from tourism, financial development, and renewable energy use to the ecological footprint is observed, alongside bidirectional causality between various factors. Policy implications emphasize the need for sustainable tourism practices and renewable energy integration. This research location's specific focus on Southeast Asia provides critical insights for policymakers aiming to balance economic growth with environmental conservation.